The Fiqh Muamalah Ijtimaiyyah Paradigm in Reconciliation of Religious Conflicts in Jayapura-Papua City - Amirullah Amirullah; Athoillah Islamy (Postgraduate Program, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
Efforts to overcome the phenomenon of social conflict between religious communities can actually refer to the universal social values contained in each religion itself. This study intends to identify the paradigm of social-community fiqh in the paradigm of reconciliation of inter-religious conflicts by Religious Harmony Forum, Jayapura City. The value of Islamic universalism and Islamic indigenization in the social-community fiqh paradigm (fiqh muamalah ijtimaiyah) formulated by Abdurrahaman Wahid became the theory of analysis in the discussion of this research. The results showed that there were dimensions of social-community fiqh (fiqh muamalah ijtimaiyah) in the paradigm of inter-religious conflict reconciliation by Religious Harmony Forum Jayapura City. First, the value of Islamic universalism in the socio-religious-based conflict reconciliation paradigm. This can be seen from inclusive religious social values such as tolerance, openness and social care in the dialogue space between interfaith leaders and community leaders regarding inter-religious harmony. Second, the value of Islamic indigenization in the cultural-based conflict reconciliation paradigm. This can be seen from the value of local wisdom that are in line with Islamic teachings in the space of religious and social aspirations. The theoretical implication of this research shows that Islamic religious social valuescan be the basis of the social-community fiqh paradigm in realizing a harmonious social life between religious communities. The limitation of the research is that it has not studied what factors are the obstacles and support for the Jayapura City Religious Harmony Forum in efforts to reconcile conflicts between religious communities.